Determination of Organic Acid Composition and Free Radical Scavenging Capacity of Kefir - Turker, Gulen; Kizilkaya, Bayram; Arifoglu, Nazan (Asian Journal of Chemistry, 2014)
The organic acid composition as well as the free radical scavenging capacity of kefir produced from different kinds of milk was investigated. The organic acid composition of the samples was determined by high performance liquid chromatography (HPLC), while free radical scavenging capacity was evaluated spectrophotometrically. Oxalic acid, acetic acid, citric acid and succinic acids were found to be significantly higher in kefir produced from cow milk (p < 0.05), while malic acid and lactic acid were significantly higher in kefir produced from goat milk (p < 0.05). The 2,2-diphenyl-1-picrylhydrazyl (DPPH) radical scavenging capacity of kefir produced from goat milk was significantly higher than that of kefir made from cow milk (p < 0.05). There was a high correlation between the malic acid and lactic acid formation and the free radical scavenging activity of the samples, implying that the formation of these organic acids during kefir production positively enhances the free radical scavenging capacity of the fermented milk products.